Classification of Transient EM Noises Depending on their Effect on the Quality of GSM-R Reception - Dudoyer, Stephen; Deniau, Virginie; Ambellouis, Sebastien; Heddebaut, Marc; Mariscotti, Andrea (IEEE transactions on electromagnetic compatibility, 2013)
The Global System for Mobile communications - Railways (GSM-R) is being deployed in different countries to develop an efficient communication-based train control (CBTC) system. GSM-R participates to achieve railways interoperability, replacing noninteroperable CBTC on existing networks and, thus, facilitating cross-border train circulations. GSM-R ensures voice and data transmissions between trains and control centers and also between trains. As any radio equipment, it is subject to electromagnetic (EM) disturbances present in the railway environment. Therefore, the quality of GSM-R transmissions can deteriorate. It is then important to evaluate and predict the effect of these disturbances in order to avoid any loss of train operational capacity. After an overview of the methods used for the characterization of the EM environment, we describe the GSM-R and the EM disturbances that can affect its operation. The reasons why the existing characterization methods are not fully adapted to the GSM-R are highlighted. The general principle of classification is briefly recalled. The rest of this paper develops the methodology proposed to perform the classification of transient EM noises and the presentation of a test bench and its associated experimental results. Finally, an application to an add-on electromagnetic compatibility supervising equipment installed on board the train is described.